We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
301
1
avatar+594 

What is (f+g)(x)?

 

f(x)=x^3−x

g(x)=x^3+2x^2−10

 Mar 6, 2018
 #1
avatar+8436 
+2

(f+g)(x)

 

=   f(x)  +  g(x)

 

=   (x3 - x)  +  (x3 + 2x2 - 10)

 

=   x3 - x + x3 + 2x2 - 10

 

=   2x3 + 2x2 - x - 10

 Mar 6, 2018

13 Online Users

avatar